Preparation and bioactivities of Cu(II) and Ni(II) complexes containing amino acid-derived schiff bases - Abas, Nur Fatihah (2017)
There is an urgent need to discover new drugs with enhanced activity, selectivity, bioavailability and fewer side effects than the current drug regime. In view of this, metal complexes containing amino acid-derived Schiff bases with potentially exciting biological activities and coordination chemistry are attractive candidates for consideration. The research reported in this thesis focused on synthesis and characterisation of new metal complexes containing amino acid-derived Schiff base. Thirty new metal complexes were synthesised from the reaction of Cu(II) chloride and Ni(II) acetate with Schiff bases derived from the condensation of amino acids (L-phenylalanine (P), L-valine (V), L-histidine (H), L-cysteine (C) and L-methionine (M) ) and different ketones (2-acetylpyrazine (2APZ), 2-acetylpyridine (2APD) and 2-benzoylpyridine (2BPD)). The synthesised complexes were characterised by various techniques including elemental analysis, molar conductance, magnetic measurements, IR, electronic spectroscopy and thermal analysis. The data obtained indicated that the amino acid-derived Schiff bases behaved as uninegatively charged tridentate NNO ligands and coordinated with the Cu(II) and Ni(II) ions via azomethine nitrogen, pyridine/pyrazine nitrogen and deprotonated carboxylate oxygen yielding stable metal complexes as evidenced in their IR Spectra. In the Cu(II) complexes, only one tridentate amino acid-derived Schiff bases was coordinated to the metal centre, while the fourth position was occupied by chloride ion. In most of the Ni(II) complexes, only one tridentate amino acid-derived Schiff bases was coordinated to the metal centre, while the fourth position was occupied by acetate ion except for [Ni(H2APZ)2].H2O, [Ni(M2APZ)2] and [Ni(M2BPD)2] complexes where they had two tridentate NNO amino acid-derived Schiff bases bonded to the metal centre. Magnetic measurements and spectral evidence supported a four coordinate geometry for Cu(II) complexes and four/six coordinate geometry for the Ni(II) complexes. The thermal analysis proved the presence of water molecules outside the coordination sphere of some of the metal complexes synthesised. The newly synthesised complexes have been screened for activity against two bladder cancer cell lines which are the invasive human bladder carcinoma cell line, EJ-28 and the minimum invasive human bladder carcinoma cell line, RT-112. It was found that the Cu(II) complexes had better cytotoxic activity against EJ-28 cells compared to RT-112 cells. In general, the Cu(II) and Ni(II) complexes containing amino acid-derived Schiff bases displayed a wide range of activity from non-active to active and could be promising candidates for selective and specific anticancer activity.